Automatic control of heat-mass exchange processes with movable distributed regulatory impact - Белоброва, Елена Владиславовна; Шейкус, Антон Романович; Корсун, Валерий Иванович (Eastern-European Journal of Enterprise Technologies, 2014)
The effect of movable distributed regulatory impact on the heat-mass exchange processes in the distillation column is investigated. It is shown that appropriate solution of the distillation process control problems can be achieved only by taking into account their qualitative specificity as an object with distributed parameters and building a new class of control systems of distributed objects with movable regulatory impact. The nature of the effect of the movable distributed regulatory impact on the controlled variables is determined. The possibility to select the allowable regulatory impact, i.e., organize heat-mass exchange processes at the right time and at a predetermined position of the distillation column is shown. One of the main advantages of movable regulatory impact is that they allow to expand the distillation unit controllability areas. The results can be used in developing static optimization and optimal distillation process control systems.